Taguchi Method-GONNS integration: Complete procedure covering from experimental design to complex optimization - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
Determination of the optimal operating conditions from the experimental data without fitting any analytical or empirical models is very convenient for manufacturing applications. In this paper, integration of Taguchi Method and Genetically Optimized Neural Networks (GONNS) is proposed. The proposed procedure covers all the steps from experimental design to complex optimization. The feasibility of the approach was evaluated by estimating the optimal cutting conditions for the milling of Ti6Al4V titanium alloy with PVD coated inserts. The test conditions were determined by the Taguchi Method. The optimal cutting condition and influences of the cutting speed, feed rate and cutting depth on the surface roughness were analyzed with the same method. GONNS estimated that the optimal cutting conditions were very close to the Taguchi Method when the same criterion was used. GONNS was also capable to minimize or maximize one of the output parameters while the others were kept within the desired range. Study demonstrated that Taguchi Method and GONNS complement each other for creation of a robust procedure for determination of the test conditions, analysis of the quality of the collected data, estimation of the influence of each parameter on the output(s) and estimation of optimal conditions with complex optimization objective functions. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Cutting forces and surface roughness; Titanium alloy; Surface milling; GONNS; Neural network; Genetic algorithm; Taguchi technique; SURFACE-ROUGHNESS; TOOL WEAR; OPERATING-CONDITIONS; CUTTING CONDITIONS; NEURAL-NETWORKS; PART I; SELECTION; PREDICTION; PARAMETERS; TITANIUM